Biopolymer colloids for controlling and templating inorganic synthesis - Preiss, Laura C.; Landfester, Katharina; Muñoz-Espí, Rafael (Beilstein Journal of Nanotechnology, 2014)
Biopolymers and biopolymer colloids can act as controlling agents and templates not only in many processes in nature, but also in a wide range of synthetic approaches. Inorganic materials can be either synthesized ex situ and later incorporated into a biopolymer structuring matrix or grown in situ in the presence of biopolymers. In this review, we focus mainly on the latter case and distinguish between the following possibilities: (i) biopolymers as controlling agents of nucleation and growth of inorganic materials; (ii) biopolymers as supports, either as molecular supports or as carrier particles acting as cores of core–shell structures; and (iii) so-called “soft templates”, which include on one hand stabilized droplets, micelles, and vesicles, and on the other hand continuous scaffolds generated by gelling biopolymers.
Keywords: biomacromolecules; biopolymer; colloid; nanoparticle; organic–inorganic hybrid; template